IMPLEMENTATION OF THE FOREIGNER REPORTING APPLICATION (APOA) TO SUPPORT IMMIGRATION LAW ENFORCEMENT IN ADDRESSING OVERSTAY CASES IN INDONESIA - Putri Meipa Liyana; Hanifa Maulidia; Mochammad Ryanindityo (Journal of Management Small and Medium Enterprises (SMEs), 2026)
The increasing number of foreign nationals overstaying their visas in Indonesia has heightened the need for effective immigration monitoring and digital governance mechanisms. This study examines the implementation of the APOA (Foreigners Reporting Application), developed by the Directorate General of Immigration, as a digital platform for accommodation providers to support immigration surveillance and improve monitoring efficiency. Using a qualitative research approach, data were collected through document analysis, immigration reports, and a comprehensive literature review. SWOT analysis was employed to evaluate the system's implementation and formulate optimization strategies. The findings indicate that APOA has enhanced digital-based supervision of foreign nationals by improving reporting efficiency and supporting immigration control processes. However, its effectiveness remains constrained by technical limitations, low compliance among accommodation providers, and insufficient integration across institutional databases. The study identifies strategic priorities for optimization, including strengthening digital infrastructure, expanding stakeholder outreach and training, improving inter-agency data integration, and enhancing surveillance and monitoring mechanisms. These findings contribute to the literature on digital public administration and immigration governance by demonstrating how integrated digital reporting systems can support more effective migration management in emerging economies while highlighting the institutional challenges that must be addressed to maximize their effectiveness. Keywords: APOA; Overstay; Immigration Surveillance; Digital Transformation; SWOT